Balloon pulmonary valvuloplasty in carcinoid syndrome. Issue 6 (1st December 2000) - Obel, O; Coltart, D J; Signy, M
Abstract : Half of all patients with carcinoid syndrome develop cardiac involvement. Patients who have cardiac involvement have a significantly worse prognosis than those without, and death can occur directly as a result of cardiac involvement. A case of carcinoid syndrome in a 38 year old woman with lesions in the liver, who presented with right sided valvar abnormalities, a dilated right ventricle, and right ventricular pressure overload, is presented. In order to palliate the patient's symptoms and to decrease right sided pressures before major abdominal surgery, balloon pulmonary valvuloplasty was performed at the time of cardiac catheterisation. This resulted in a reduction in the pulmonary gradient and right ventricular pressure. Following the procedure, the patient's symptoms were completely relieved. She went on to laparotomy where the lesions in the liver were excised without complication.